2020
DOI: 10.15252/embr.202050733
|View full text |Cite
|
Sign up to set email alerts
|

Function of the SNARE Ykt6 on autophagosomes requires the Dsl1 complex and the Atg1 kinase complex

Abstract: The mechanism and regulation of fusion between autophagosomes and lysosomes/vacuoles are still only partially understood in both yeast and mammals. In yeast, this fusion step requires SNARE proteins, the homotypic vacuole fusion and protein sorting ( HOPS ) tethering complex, the RAB 7 GTP ase Ypt7, and its guanine nucleotide exchange factor ( GEF ) Mon1‐Ccz1. We and others recently identified Ykt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 109 publications
0
26
0
2
Order By: Relevance
“…However, in Ykt6-3E overexpressing cells, those endosomes were significantly smaller than in Ykt6-WT ( Figure 5 B), indicating that the mutated SNARE domain might hinder endosomal fusion events activated by Rab5Q79L. Interestingly, under serum-fed conditions, Ykt6 had no effect on the levels of p62, as a readout of autophagy induction ( Figure 5 C), suggesting that the non-canonical role of Ykt6 in autophagy could be starvation-dependent [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in Ykt6-3E overexpressing cells, those endosomes were significantly smaller than in Ykt6-WT ( Figure 5 B), indicating that the mutated SNARE domain might hinder endosomal fusion events activated by Rab5Q79L. Interestingly, under serum-fed conditions, Ykt6 had no effect on the levels of p62, as a readout of autophagy induction ( Figure 5 C), suggesting that the non-canonical role of Ykt6 in autophagy could be starvation-dependent [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Under normal growth conditions, these processes seem to be more important for cellular function, than its role in autophagosome formation. As it has also been reported that Ykt6 is involved in autophagosome–lysosome fusion in human cells and Drosophila fat body under starvation-induced conditions [ 15 , 19 ], it is possible that Ykt6 is allocated to alternate compartments, especially under nutrient stress condition [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stx17 has been shown to play a role during autophagy initiation by assembling protein complexes necessary for the preautophagosomal structure (mPAS) ( 46 ). Moreover, it was recently shown that in yeast, phosphorylation of Ykt6 by Atg1 kinase also plays an inhibitory role during autophagosome formation, and dephosphorylation of Ykt6, by an unknown phosphatase, is necessary to complete autophagosome formation ( 47 ). Our data fit with these observations and suggest a model in which the Ca 2+ -CaN cascade posttranslationally regulates the early phases of autophagy through regulation of Ykt6 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion of autophagosomes with the lytic compartment requires the R-SNARE Ykt6 in both yeast and mammals [179][180][181]. Ykt6 is directly phosphorylated at Ser182 and Ser1832 by Atg1, and another Ytk6 phosphorylation site was identified at Thr158 (Figure 2, Table 1) [53,182,183]. Phosphorylation of these sites inhibits autophagosome-vacuole fusion by preventing Ykt6 bundling with the vacuolar Q-SNAREs Vam3 and Vti1 [182,183].…”
Section: Phosphoregulation During Autophagosome-vacuole/ Lysosome Fusionmentioning
confidence: 99%